Quasi-steady-state chemical exchange saturation transfer (QUASS CEST) MRI analysis enables T(1) normalized CEST quantification - Insight into T(1) contribution to CEST measurement - Sun, Phillip Zhe (J Magn Reson, 2021)
Chemical exchange saturation transfer (CEST) MRI depends not only on the labile proton concentration and exchange rate but also on relaxation rates, particularly T(1) relaxation time. However, T(1) normalization has shown to be not straightforward under non-steady-state conditions and in the presence of radiofrequency spillover effect. Our study aimed to test if the combined use of the new quasi-steady-state (QUASS) analysis and inverse CEST calculation facilitates T(1) normalization for improved CEST quantification. The CEST signal was simulated with Bloch-McConnell equations, and the apparent CEST, QUASS CEST, and the inverse CEST effects were calculated. T(1)-normalized CEST effects were tested for their specificity to the underlying CEST system (i.e., labile proton ratio and exchange rate). CEST experiments were performed from a 9-vial phantom of independently varied concentrations of creatine (20, 40, and 60 mM) and manganese chloride (20, 30, and 40 μM) under a range of RF saturation amplitudes (0.5–4 μT) and durations (1–4 s). The simulation showed that while T(1) normalization of the apparent CEST effect was subject to noticeable T(1) contamination, the T(1)-normalized inverse QUASS CEST effect had little T(1) dependence. The experimental data were analyzed using a multiple linear regression model, showing that T(1)-normalized inverse QUASS analysis significantly depended on creatine concentration and saturation power (P<0.05), not on manganese chloride concentration and saturation duration, advantageous over other CEST indices. The QUASS CEST algorithm reconstructs the steadystate CEST effect, enabling T(1)-normalized inverse CEST effect calculation for improved quantification of the underlying CEST system.